2017
DOI: 10.1007/s00210-017-1359-2
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase: its potential role in promotion of pulmonary arterial hypertension

Abstract: NADPH oxidases (NOXs) are a group of enzymes for superoxide anion (O ) generation through transferring electrons from NADPH to molecular oxygen, which is rapidly converted into hydrogen peroxide (HO). There are seven members in NOX family, including NOX1 to NOX5, dual oxidase1, and dual oxidase 2. Recent studies have demonstrated that NOX subtypes may have different functions in different types of pulmonary arterial hypertension (PAH). The NOX-derived reactive oxygen species (ROS) are key factors that are invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Studies from other labs and ours have repeatedly demonstrated that NOX-derived ROS contributes greatly to myocardial/cerebral ischemic injury [8][9][10], endothelial dysfunction [11,12], and vascular remodeling [13,14]. There is growing evidence that NOX is activated in animals or humans with PAH, indicating that NOX-derived ROS may contribute to the development of PAH [15][16][17]. Furthermore, our previous studies have demonstrated that NOX coordinates with vascular peroxidase 1 (VPO1) to amplify the role of NOX-derived ROS in mediation of oxidative injury in myocardial ischemia/reperfusion injury and vascular remodeling in PAH [6,18] because VPO1 can catalyze NOX-derived hydrogen peroxide (H 2 O 2 ) to produce more powerful oxidant hypochlorous acid (HOCl).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Studies from other labs and ours have repeatedly demonstrated that NOX-derived ROS contributes greatly to myocardial/cerebral ischemic injury [8][9][10], endothelial dysfunction [11,12], and vascular remodeling [13,14]. There is growing evidence that NOX is activated in animals or humans with PAH, indicating that NOX-derived ROS may contribute to the development of PAH [15][16][17]. Furthermore, our previous studies have demonstrated that NOX coordinates with vascular peroxidase 1 (VPO1) to amplify the role of NOX-derived ROS in mediation of oxidative injury in myocardial ischemia/reperfusion injury and vascular remodeling in PAH [6,18] because VPO1 can catalyze NOX-derived hydrogen peroxide (H 2 O 2 ) to produce more powerful oxidant hypochlorous acid (HOCl).…”
Section: Introductionmentioning
confidence: 86%
“…Although NOX inhibitors, such as apocynin and diphenyleneiodonium (DPI), showed therapeutic effects on PAH animals [17], they lacked clinical value due to the nonspecific effect and unacceptable toxicity. Actually, the efforts to seek ideal NOX inhibitors, particularly from Chinese traditional herbs, for prevention and therapy of PAH have never stopped.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of Nox2 in PAH is supported by even a larger body of literature [87,93] and was shown to be involved in pulmonary artery vasoconstriction, smooth muscle remodeling, and RV hypertrophy [94,95]. Interestingly, hypoxia-induced activation and membrane translocation of p47phox subunit of Nox2 in pulmonary but not mesenteric arteries [96] suggests the unique function of Nox2 in hypoxic pulmonary vessels compared to the systemic circulation.…”
Section: Sources Of Ros In Pah and The Role Of Gendermentioning
confidence: 99%
“…NOX5‐derived ROS have been implicated in a number of pathologies, especially cardiovascular disease, renal disease and cancer. Other pathologies, such as neurodegenerative diseases (Tarafdar & Pula, ), pulmonary arterial hypertension (Peng, Liu, Xu, Peng, & Luo, ) and liver fibrosis (Andueza et al., ), have also been linked to NOX5, but there is very little supporting evidence for this.…”
Section: Pathophysiology Of Nox5mentioning
confidence: 99%